The Influence of Digital Marketing and Brand Image on Local Product Purchase Decisions Among Gen Z - Zulkarnain, Muhammad Qadafi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study aims to analyze the influence of digital marketing and brand image on the purchase decisions of local products among Generation Z. A quantitative approach was employed using an online survey, targeting Generation Z consumers who have previously purchased local products. The sample was selected purposively, and the data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The number of respondents needed is around 150–250. The findings indicate that digital marketing positively affects purchase decisions both directly and indirectly through brand image as a mediating variable. Brand image plays a crucial role in strengthening the relationship between digital marketing activities and purchase behaviour. The novelty of this study lies in its focus on Generation Z's purchasing patterns within the context of Indonesian local products. The study suggests that businesses should optimize authentic, interactive digital marketing strategies to enhance their brand image.